RETRACTED ARTICLE: Unraveling the influence of TiO2 nanoparticles on growth, physiological and phytochemical characteristics of Mentha piperita L. in cadmium-contaminated soil - Hamid Mohammadi; Zahra Kazemi; Ahmad Aghaee; Saeid Hazrati; Rosa Golzari Dehno; Mansour Ghorbanpour (Scientific Reports, 2023)
Abstract Among the metals contaminants, cadmium (Cd) is one of the most toxic elements in cultivated soils, causing loss of yield and productivity in plants. Recently, nanomaterials have been shown to mitigate the negative consequences of environmental stresses in different plants. However, little is known about foliar application of titanium dioxide nanoparticles (TiO2 NPs) to alleviate Cd stress in medicinal plants, and their dual interactions on essential oil production. The objective of this study was to investigate the effects of foliar-applied TiO2 NPs on growth, Cd uptake, chlorophyll fluorescence, photosynthetic pigments, malondialdehyde (MDA) and hydrogen peroxide (H2O2) contents, total phenols, anthocyanins, flavonoids, antioxidant enzymes (SOD, CAT and POD) activity and essential oil content of Mentha piperita L. (peppermint) under Cd stress. For this purpose, plants were grown in Cd-contaminated (0, 20, 40, and 60 mg L−1) soil, and different concentrations of TiO2 NPs (0, 75, and 150 mg L−1) were foliar sprayed at three times after full establishment until the beginning of flowering. Exposure to TiO2 NPs significantly (P < 0.01) increased shoot dry weight (37.8%) and the number of lateral branches (59.4%) and decreased Cd uptake in plant tissues as compared to the control. Application of TiO2 NPs increased the content of plastid pigments, and the ratio Fv/Fm (13.4%) as compared to the control. Additionally, TiO2 NPs reduced the stress markers, MDA and H2O2 contents and enhanced the activity of the phenylalanine ammonia-lyase (PAL) enzyme (60.5%), total phenols (56.1%), anthocyanins (42.6%), flavonoids (25.5%), and essential oil content (52.3%) in Cd-stressed peppermint compared to the control. The results also demonstrated that foliar spray of TiO2 NPs effectively improved the growth and chlorophyll fluorescence parameters and reduced Cd accumulation in peppermint, which was mainly attributed to the reduction of oxidative burst and enhancement of the enzymatic (SOD, CAT, and POD) antioxidant defense system due to the uptake of NPs. The findings provide insights into the regulatory mechanism of TiO2 NPs on peppermint plants growth, physiology and secondary metabolites production in Cd-contaminated soil.